1998
DOI: 10.1186/cc119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nosocomial pneumonia on the outcome of mechanically-ventilated patients

Abstract: Background:Nosocomial pneumonia (NP) is a common complication in mechanically-ventilated patients and is considered to be one of the most common causes of morbidity and mortality. However, assessment of the associated mortality is not staightforward as it shares several risk factors with NP that confound the relationship. The aim of this study was to evaluate the impact of NP on the mortality rate in an intensive care unit. During the study period (January-December 1995) all patients under mechanical ventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is also the most serious complication of MV, as it contributes to an increase in patient mortality, morbidity, length of hospital stays, and financial cost. 8 , 9 , 10 Since VAP occurs in critically ill patients, it is difficult to determine the exact mortality of VAP. However, Melson et al 11 have reported that VAP has an estimated attributable mortality rate of 13%.…”
Section: Introductionmentioning
confidence: 99%
“…It is also the most serious complication of MV, as it contributes to an increase in patient mortality, morbidity, length of hospital stays, and financial cost. 8 , 9 , 10 Since VAP occurs in critically ill patients, it is difficult to determine the exact mortality of VAP. However, Melson et al 11 have reported that VAP has an estimated attributable mortality rate of 13%.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, established empiric antibiotic strategies for patients with sepsis due to postoperative abdominal infections include single- and multiple-agent regimens [21,34,35,36]. Recommended regimens for therapy of nosocominal sepsis without knowledge of the presumable pathogen are carbapenems (imipenem/cilastatin or meropenem) and piperacillin plus tazobactam.…”
Section: Therapy Of Postoperative Bacterial/fungal Infectionsmentioning
confidence: 99%